Characterization of Novel Cellulosic Salvadora Persica Fiber for Potentiality in Polymer Matrix Composites - Jamaluddin Hindi; Abdul Ajees Abdul Salam; Muralishwara K; Gurumurthy B M; Shivaprakash Y M; Ayman Ibrahim (Journal of Natural Fibers)
Natural fiber is expected to make polymer composites light and environmentally friendly. In this paper Salvadora persica natural fiber is characterized in view of its use in composite materials for the first time. Average diameter of the fiber was 250 µm and density was 1.3 g/cm3. The surface of the fiber was irregular with impurities and surface features such as shallow tubs, cell walls and lignin were revealed by Scanning Electron Microscopy (SEM). X-ray diffraction (XRD) analysis reveals Crystallinity Index (C.I) of 58% and Crystallite Size of 3.58 nm. The chemical bonds pertaining to different constituents of the natural fiber such as cellulose, hemicellulose and lignin were identified by Fourier Transform Infrared (FTIR) spectroscopic analysis. In the thermal degradation of the fiber during the Thermogravimetric analysis (TGA), three stages were identified. The maximum thermal degradation temperature (Tfinal) was determined to be 357°C. Tensile strength, Young’s modulus and percentage elongation of the fiber were 430 ± 100 MPa, 16 ± 3.9 GPa and 4.2 ± 0.91% respectively.